Pacific-Gondwana Permo-Triassic Orogenic Belt with Lesser Overprinted Cenozoic Deformation, Eastern Bird Head Peninsula, West Papua, Indonesia - Sukahar Eka Adi Saputra; Christopher L. Fergusson (Geological Agency, 2023)
The Paleozoic to Early Mesozoic Pacific-facing active margin of East Gondwana has been shown to extend into the Kemum Block of northern Bird Head Peninsula (western New Guinea), and was associated with Mid Paleozoic orogenic deformation and Devonian to Triassic silicic magmatism and foreland basin deposition. In the Mawi Bay area of the eastern Bird Head Peninsula, the (?) Permian Mawi Complex is a multiply-deformed unit with a pre-Late Triassic D1 deformation formed in an Andean back-arc setting associated with active margin tectonism. The D1 deformation is characterized by recumbent, isoclinal to tight, north-northeast facing folds with an axial planar S1 cleavage formed at a low metamorphic grade, and predated the unconformably overlying Upper Triassic - Middle Jurassic Tipuma Formation. South of the Mawi Complex, the Mesozoic-Paleogene succession of the northern Lengguru Fold Belt is affected by north-northwest trending folds, cleavage, and most of the succession dips moderately to gently to the west-southwest. This deformation is reflected in the underlying Mawi Complex by northwest-trending D2 structures that have folded the D1 folds, and have steeply inclined open to gentle folds, some polyclinal folds, and fault-related folds. The structures in the northern Lengguru Fold Belt may have influenced The Pliocene to Quaternary Central Bird Head Monocline associated with the Kemum Block uplifting in the northern Bird Head Peninsula